스테인리스강 316L 배관의 End Grain Attack과 피트부식 손상진단 - 백운봉; Un Bong Baek; 최병학; Byung Hak Choe; 이진희; Jin Hee Lee; 심종헌; Jong Hun Shim; 김의수; Eui Soo Kim; 남승훈; Sung Hoon Nam (대한금속·재료학회지, 53(1), 2015)
The aim of this paper was to analyze the cause of surface cracks and pit corrosion on 316L pipe. An End Grain Attack (EGA) as a kind of pit mechanism was conducted on the pipe surface. The early stage of the EGA may come from under-deposit of caustic-water formation compositions like Na+, K+, Ca+, and Mg+ etc. The under-deposit corrosion is caused by the corrosion layer on the pipe surface followed by crevice corrosion due to accumulation of Cl-or S-composition between the corrosion layer and the pipe surface. In the early stage, the EGA occurred in all grain boundaries beneath the under-deposit corrosion. In the later stage of EGA, almost all the early attacked grain boundaries stopped at a limited depth of about 10 μm. Meanwhile, only the smallest number of the attacked boundaries progressed into the pipe as pit corrosion and resulted in leak failure. (Received February 24, 2014)